Synthesis of Carbonyl Compounds by Gold-Catalyzed Carbonylation Reactions - Cao, Yanwei; He, Lin (Synlett, 2022)
In recent years, carbonylation reactions has experienced rapid progress and has become the essential and efficient strategies for the large-scale preparation of carbonyl compounds. Although palladium, rhodium, iridium, ruthenium, and cobalt are the dominating catalysis in carbonylation reactions, the gold has emerged as a selectable catalysis in some specific carbonylation reactions in the past two decades. Both homogeneous and heterogeneous gold catalysis have been studied in carbonylation reactions. Herein, we briefly reviewed the history of gold-catalyzed carbonylation reactions, including carbonylation of olefins, methanol, and amines. It also highlights our recent works on synergistic Au/Cu-catalyzed oxidative carbonylation of amines.1 Introduction2 Carbonylation of Olefins3 Carbonylation of Methanol4 Carbonylation of Amines4.1 Gold Catalysis4.2 Bimetallic Au–M catalysis5 Conclusion and Outlook
Keywords: gold; catalysis; carbonylation; olefins; methanol; amines